On Regional Original Income In The Province South Sulawesi 2018-2020 - Chairul Iksan Burhanuddin; Amran Amran; Muhammad Nur Abdi Muhammad Nur Abdi; Arab Mustari’ba Arab Mustari’ba (Journal Of Social Science (JoSS), 2022)
This study aims to determine the effect of taxes, levies and population on local revenue in South Sulawesi Province in 2018-2020.This study uses quantitative methods.The population in this study were all regencies/cities in the research year totaling 24 regencies/cities.The sampling technique used a saturated sample,the sampling technique was used when all members of the population were sampled,so that a total sample of 24 samples was obtained.This type of research data is secondary data obtained through reports or publications from related agencies that are closely related to this research.The results of the study show that taxes,levies and the number of residents simultaneously have an effect on Regional Original Income.And the Tax Variable partially affects Regional Original Income while the Levies and Population Variables partially have no effect on Regional Original Income in South Sulawesi Province 2018-2020.